Total synthesis of polyunsaturated DHA-like methoxylated ether lipid - Einar Lúthersson 1986- (2013)
Nonpolar ether lipids of 1-O-alkyl-2,3-diacyl-sn-glycerol type are major constituents of the liver oils of shark, dogfish and various other species of elasmobranch fish. Methoxyl substituted alkylglycerols of the (2’R)-1-O-(2’-methoxyalkyl)-sn-glycerol type are a very interesting subgroup of the ether lipids that possess a methoxyl group located at the 2-position of the 1-O-alkyl chain. They were discovered and isolated in the late 1970s from Greenland shark liver oil, where they account for 4% of the total amount of the glyceryl ethers, and they have been claimed to display various interesting biological activities. Some years after their discovery a fascinating docosahexaenoic acid (DHA) like methoxylated alkylglycerol, an all-cis-(2'R)-1-O-(2´-methoxy-4,7,10,13,16,19-docosahexaenyl)-sn-glycerol was found in Greenland shark liver oil. The work described in this thesis reveals our attempts to synthesize this fascinating DHA-like methoxylated ether lipid possessing two stereogenic centres and the omega-3 polyunsaturated methylene interrupted all-cis hexaene framework by a highly convergent synthesis. Our first attempt was based on attaching a tetrayne tail part building block to a middle part diyne building block possessing a chlorohydrin moiety by a copper promoted coupling reaction which was successfully executed. The tetrayne tail part was synthesized by use of efficient successive copper promoted coupling reactions involving propargyl bromides. The middle part diyne was also successfully synthesized by use of (R)-epichlorohydrin as a chiral precursor. The resulting chlorohydrin hexayne was submitted to partial hydrogenation by use of a Lindlar catalyst and although there is no question that the majority of the material was being converted to the desired hexaene there were strong indications of an overhydrogenation taking place such that a significant part of the material got hydrogenated beyond the all-cis hexaene level. Attachment of the second chiral starting material (R)-solketal to the chlorohydrin ...